Individualized frequency and montage tACS to engage theta-gamma coupling and enhance working memory in mild cognitive impairment - Mirjalili, Mina; Palamarchuk, Iryna S.; Brooks, Heather; Zomorrodi, Reza; Melichercik, Ashley; Wang, Wei; Nestor, Sean M.; Blumberger, Daniel M.; Datta, Abhishek; Bowie, Christopher; Mdawar, Bernadette; Hynynen, Kullervo; et al. (Frontiers in Psychiatry, 2025)
Mild Cognitive Impairment (MCI) is a clinical prodromal stage of Alzheimer’s disease. Enhancing executive functions in patients with MCI could optimize cognitive compensatory mechanisms and slow cognitive decline. The prefrontal cortex (PFC) and its connections to the hippocampus support executive functions, including working memory. Transcranial alternating current stimulation (tACS) can modulate these connections by engaging theta-gamma coupling (TGC) and may thereby strengthen working memory. This study, “tACS to engage theta-gamma coupling and enhance working memory in MCI” (tACS-MCI), will assess the feasibility and cognitive effects of EEG and MRI-guided individualized tACS. The stimulation will target the prefrontal and temporal cortices in 20 MCI participants. Participants will be randomized to receive either individualized tACS or sham tACS for 10 days. tACS individualization will involve adjusting the theta frequency, tACS electrode locations, and current intensity for each participant. Cognitive and functional assessments will occur at baseline and post-intervention. We aim to determine: 1) the feasibility of individualized tACS in MCI, including recruitment and retention; 2) whether tACS engages TGC by assessing its increase in response to tACS; and 3) changes in N-back working memory performance following tACS, as well as whether changes in TGC mediate the changes in performance. The tACS-MCI study will employ an EEG and MRI-guided individualized approach to promote synchronization between frontal and temporal cortices, using participant’s unique brain structure and neurophysiology. We aim to assess the feasibility of this novel intervention as a potential approach to more effectively prevent cognitive decline.